Femtosecond Laser Implantation of a 355-Degree Intrastromal Corneal Ring Segment in Keratoconus: A Three-Year Follow-Up - Marwa Mahmoud Abdellah; Hatem Gamal Ammar (Journal of Ophthalmology)
Purpose. To evaluate the outcomes of femtosecond laser-assisted implantation of a 355-degree intracorneal ring (ICR) (Keraring) in patients with keratoconus in the three-year follow-up. Setting. Future Femtolaser Center, Sohag, Egypt. Design. Prospective interventional case series. Patients and Methods. A prospective case series of 38 eyes of 26 patients with keratoconus had implantation of the 355-degree ICR keraring after tunnel creation with a femtosecond laser. The uncorrected visual acuities (UCVA) and best-corrected visual acuities (BCVA), sphere, cylinder, and manifest refraction spherical equivalent (SE), and mean keratometry (K), K max, and K min were evaluated preoperatively and 3, 6, 12, 24, and 36 months postoperatively, and all complications were reported. Results. 38 eyes of 26 patients with mean age 25.92 ± 5.44 years were enrolled in the study, 11 were males (42.3%). The mean UCVA improved from 0.93 ± 0.21 to 0.63 ± 0.21 logMAR (P≤0.001) and the mean BCVA from 0.67 ± 0.22 to 0.43 ± 0.26 logMAR (P<0.001). The mean sphere, cylinder, and spherical equivalent have been changed dramatically from preoperative to 3 month postoperative, which is statistically significant (P≤0.001), and the changes between 1 and 2 years and 2 and 3 years are also considerable and statistically significant; the K max and K min and K mean improved and the changes were statistically significant (P≤0.001), and the changes between one, two, and three years were also statistically significant. The safety and efficacy indices were changed through the three-year follow-up. The complications were corneal neovascularization (36.84%), corneal melting (26.3%), and ring extrusion (31.5%) at the end of the study. Conclusions. Implantation of a 355-degree intracorneal keraring using femtosecond laser improved the visual, refractive, and topographic parameters in keratoconus patients, with a high rate of ICR extrusion and instability. The study has been registered for the Pan African Clinical Trial Registry (http://www.pactr.org) database within No: PACTR201810796878908 on 29 October 2018.